Yearly weather variation and surface temperature drives the spatiotemporal dynamics of a threatened butterfly and its host plant - Franzén, Markus; Francioli, Yannick; Askling, John; Kindvall, Oskar; Johansson, Victor; Forsman, Anders (Frontiers in Ecology and Evolution, 2022)
It remains unclear to what extent yearly weather variation and spatial variation in microclimate influences the outcome of interacting plant-animal species and whether responses differ between life stages. We collected data over several years on 46 hectares on File Hajdar, Gotland, Sweden, and executed a complete mapping of larva nests (n = 776) and imago (n = 5952) of the marsh fritillary butterfly Euphydryas aurinia and its host plant Succisa pratensis. The phenology of the butterflies and the major nectar plants visited varied among years. The duration of the adult flight period decreased with increasing ambient air temperatures. The density of butterflies, host plants and host plant leaf size increased between years with increasing precipitation in the preceding year, and decreased with increasing average ambient temperature in the preceding year. In 2021 and 2022 we deployed a UAV with a high-resolution thermal sensor to measure spatial variation in surface temperatures in the study area. We found that survival from the egg to the larva stage increased with increasing surface temperature and host plant density. Host plants and larva nests generally occupied warmer microhabitats compared to imago butterflies. The results further suggested that the relationships linking surface temperature to the densities of imago, larva, host plants, and leaf size differed qualitatively between years. In 2017, larva nests and host plant density increased with increasing surface temperatures, and butterflies showed a nonlinear response with a density peak at intermediate temperatures. As a result of the extreme drought in 2018 there was a reduction in maximum leaf size, and in the densities of plants, larvae and butterflies. Moreover, the slopes of the relationships linking the density of larvae, butterflies, and plants to temperature shifted from linear positive to negative or curvilinear. Our findings demonstrate how yearly weather variation and heterogeneous surface temperatures can drive the spatiotemporal distribution and dynamics of butterflies and their host plants. The context specificity of the responses indicated by our results makes it challenging to project how climate change will affect the dynamics of ecological communities.